Tracking Spontaneous Vestibular Schwannoma Regression with Volumetric Measurements. (26th October 2020) - Patel, Evan J.; Deep, Nicholas L.; Schecht, Michael; Hagiwara, Mari; Roland, John T.
Abstract : Objective: To characterize a series of patients with MRI evidence of spontaneous vestibular schwannoma (VS) regression. Study Design: Retrospective case series. Methods: Retrospective review between 2012 and 2020 from a single, tertiary‐care center of all patients with an untreated, sporadic VS and spontaneous regression in volumetric tumor size over the course of observation. The main outcome measures included VS size and location, presenting symptoms, medication use, changes in pure‐tone averages and word recognition scores. Results: The 13 treatment‐naïve patients (62% female, mean age 67.1 years) with spontaneous VS regression represented 3.9% of all patients undergoing observation with serial imaging during the study period. Median tumor size from initial MRI was 529.0 mm 3 (range: 108 mm 3 –13, 180 mm 3 ). The mean interval between MRI measurements was 5.5 years (SD 4.4 years). The average percent decrease in tumor size was 36.1% (SD 21.9%) and the average rate of volume decrease was 15.8 mm 3 /yr (SD 25.4 mm 3 /yr). Five patients were classified as having major regression, defined by a relative decrease in volume of >40%, while eight patients had minor regression (<40% relative volume reduction). No significant differences in initial tumor size, rate of regression, or audiometric changes were observed between the major and minor regression cohorts. Conclusions: Patients with evidence of a spontaneously shrinking VS have a heterogeneous presentation. Due to the scarcity of this phenomenon, predicting which tumors will eventually undergo regression remains unclear. Employing volumetric measurements to compare serial MRI scans may improve the accuracy of detecting shrinking tumors. Level of Evidence: 4 Laryngoscope, 131:E1647–E1652, 2021